Cataracta, a new monotypic genus segregated from Physalis (Solanaceae) - Zamora-Tavares, Pilar; Martínez, Mahinda; Vargas-Ponce, Ofelia (Phytotaxa, 2023)
We describe a new monotypic genus Cataracta based on Physalis microphysa. From 1896 to 2016, five different authors have pointed out that removing P. microphysa from Physalis may contribute to the monophyly of the genus. Recent phylogenetic analyses showed that P. microphysa does not share the most recent common ancestor with Physalis, and its taxonomic position remained uncertain. Therefore, this taxonomic change is necessary. The diagnostic traits of Physalis microphysa are the fruiting calyx that loosely covers the fruit, remaining open apically, with lobes as long as, or longer than the tube, a dry berry with thin pericarp, and a dehiscent epicarp covered by a thick cuticle. In contrast, Physalis species with typical morphologies have an inflated and completely closed fruiting calyx at the apex that fully envelopes the fleshy berry. The anatomical evidence and molecular phylogenetic analysis with six cpDNA and three nDNA regions performed with Maximum Likelihood and Bayesian Inference confirm that P. microphysa can be recognized as a distinct genus from Leucophysalis, Physalis and Quincula. Cataracta gen. nov. is sister to Chamaesaracha and along with the closely related Quincula grows in arid to semi-arid environments in Mexico and North America. An artificial key to Physalidinae genera is included.